Cross-border ties and the reproductive health of India's internal migrant women. (December 2016) - Sudhinaraset, May; Melo, Jason; Diamond-Smith, Nadia
Abstract: The literature on how social ties influence sexual and reproductive health is well established; however, one significant limitation of this research is the influence of social ties to hometowns among migrant women. Drawing from cross-border social ties literature, the objective of this study is to assess how cross-border social ties influence use of family planning and institutional deliveries among internal migrant women in India. Cross-sectional data come from 711 migrant women living in slums in Uttar Pradesh, India. Multivariable logistic regression was used to assess odds of modern use of family planning and odds of institutional deliveries with cross-border tie indicators. Results suggest that higher cross-border ties were associated with 2.35 times higher odds of family planning use ( p <0.1) and 2.73 times higher odds of institutional delivery ( p <0.05). This study suggests that social ties to hometowns may serve as a protective factor, possibly through increased social support, to migrants in regards to reproductive decision-making and use of reproductive health services. Future studies should explore potential mechanisms for these findings. Highlights: Cross-border ties are common among internal migrant women in Lucknow, India. Cross-border ties is associated with increased family planning use and institutional delivery. Remitting money is associated with increased family planning use.